Modeling Soft Dimensions of FMS and Their Interrelationship Using ISM and MICMAC Analysis - Bag, Surajit; Anand, Neeraj (Prabandhan: Indian Journal of Management, 2015)
India is emerging as a major manufacturing hub next to China for a large number of industrial products due to the availability of resources, large qualified workforce, emerging new markets, and low cost of production. The objective of the present study was to identify the interrelationship and links between soft dimensions of a flexible manufacturing system, whose richness plays a vital role in successful FMS implementation. Thorough literature review is presented on a flexible manufacturing system. Not only do the latest technologies involving automation and robotics in manufacturing drive operational excellence and improve productivity, but the role of human factors or soft dimensions is also crucial, and needs to be considered for the successful implementation of a flexible manufacturing system. Its implementation would enable any manufacturer to survive in this competitive environment where sustainability is achieved by adopting a flexible manufacturing system. A flexible manufacturing system reduces set up time, provides more flexibility, and leads to standardization of processes. An efficient manufacturing system rooted in sustainability is the key to improve profitability in this uncertain business environment. The present study employed ISM methodology and MICMAC analysis to identify the contextual interrelationships between soft dimensions of FMS. The dependent and independent factors identified from the study will help managers and decision makers in enhancing productivity and profitability.